2008
DOI: 10.1038/sj.leu.2405090
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between cotransplantation of mesenchymal stem cells and higher recurrence rate in hematologic malignancy patients: outcome of a pilot clinical study

Abstract: In this open-label randomized clinical trial, HLA-identical sibling-matched hematopoietic stem cells (HSC) were transplanted (non-MSCs group, n ¼ 15) or cotransplanted with mesenchymal stem cells (MSCs) (MSCs group, n ¼ 10) in hematologic malignancy patients. The median number of MSCs infused was 3.4 Â 10 5 kg À1 (range, 0.3-15.3 Â 10 5 kg À1 ). MSCs infusions were well tolerated. The median time to neutrophil engraftment (absolute neutrophil count 40.5 Â 10 9 l À1 ) was 16 days for MSCs group and 15 days for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
262
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(273 citation statements)
references
References 37 publications
(33 reference statements)
6
262
3
2
Order By: Relevance
“…We have read with interest the paper by Ning et al 1 reporting a correlation between the cotransplantation of mesenchymal stem cells (MSCs) in allogeneic haemapoietic stem cell transplantation and a higher recurrence rate of malignant haematologic diseases. The authors concluded their paper by suggesting that 'the use of MSCs must be handled with extreme caution before a large-scale trial is performed'.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We have read with interest the paper by Ning et al 1 reporting a correlation between the cotransplantation of mesenchymal stem cells (MSCs) in allogeneic haemapoietic stem cell transplantation and a higher recurrence rate of malignant haematologic diseases. The authors concluded their paper by suggesting that 'the use of MSCs must be handled with extreme caution before a large-scale trial is performed'.…”
mentioning
confidence: 75%
“…1,2 We further proposed that Notch pathway inhibition in MM cells is a promising new therapeutic approach as it controls Notch ligand-induced myeloma cell growth. 1 We and others provided evidence that Notch receptors are expressed on primary MM cells and that Notch ligands on MM and bone marrow stroma cells activate Notch signaling through homotypic as well as heterotypic interactions in MM cells. 1,3 In addition, Houde et al 4 published that the Notch ligand, JAG2, is overexpressed in myeloma cells and activates Notch signaling in bone marrow Letters …”
mentioning
confidence: 99%
“…Although these encouraging results support an effect of infused MSCs in the prevention of GVHD, an increased occurrence of leukemia relapses has been reported because of the inhibition of leukemic cell-specific T-cell responses. 85 MSCs from human autoimmune disease Autologous BM-derived MSCs have been shown to be potently antiproliferative to stimulated T-cells from normal participants and autoimmune (RA, SSc, Sjoegren's, SLE) patients, 86 and in SSc patients these MSCs were normal with respect to proliferation, clonogenicity and differentiation to bone and fat. 87 However, one group has shown defective differentiation into endothelial precursors in BM-derived MSCs from SSc patients, 88 which should be considered when choosing autologous or allogeneic MSC sources for SSc treatment.…”
Section: Mscs and Human Experiencementioning
confidence: 99%
“…Co-transplantation of BM-MSCs was found to be associated with a higher rate of occurrence of leukemic relapse. 24 BM-MSCs have also been suggested to be involved in the progression of oncogenesis in multiple myeloma, 25 which can be mediated by MSC-derived exosomes. 26 The anticipation of using BM-MSCs as GVHD treatment dramatically declined in the scientific community when the negative results of the randomized clinical trial by Osiris Therapeutics were released.…”
Section: Introductionmentioning
confidence: 99%